Strategi Efektif dalam Manajemen Organisasi Pendidikan untuk Meningkatkan Kinerja Sekolah - Ahmad Mukhlasin; Anisa May Azura; Kania Anisah; Khairia Zara (STIKes Ibnu Sina Ajibarang, 2024)
This article aims to examine various effective strategies in the management of educational organizations that can be implemented to improve school performance. The focus of the discussion covers important aspects of school management, such as educational leadership, human resource management, curriculum and learning management, infrastructure management, financial management, and school relations with the community. The qualitative approach used in this research allows researchers to gain an understanding in depth about effective management strategies in improving school performance. By exploring the experiences and views of school leaders and teachers, it is hoped that this research will provide valuable insights that can be used to develop better management practices in other schools. The results of this research reveal that effective management strategies in improving school performance include visionary and inclusive leadership, effective human resource management, positive organizational culture, optimal use of information technology, parent participation, and the ability to adapt and innovate. These findings provide valuable insights that can be used by other schools to develop better management practices and improve overall educational performance. In addition, it is hoped that the results of this research can serve as a guide for educational policy makers in formulating policies that support improving school performance through effective management.